Utilization of Construction Concrete Waste as Aggregate Substitutes in Normal Concrete Production - Zulkarnain, Iskandar; Asnaning, Aniessa Rinny; Desniati, Emmi; Balqis, Tanya Audia (ABEC Indonesia, 2024)
The construction process frequently necessitates the demolition of existing structures, resulting in substantialconstruction waste. A significant portion of this waste comprises demolition debris, particularly from concrete buildingmaterials. This research aims to develop standard concrete by partially substituting conventional coarse and fineaggregates with concrete waste materials. The substitutions involved replacing 25% and 50% of sand and gravel,respectively, by weight, using a K300 concrete mix design. Adopting the SNI 03-2834-2000 method, the mix design for 1cubic meter of concrete comprised cement (528 kg), sand (776.16 kg), gravel (807.04 kg), and water (205 kg). Theresults indicated an average sample weight reduction, with the first sample at 12.91 kg, the second at 12.79 kg, and thethird at 12.77 kg. This weight decrease suggests that using waste as a partial aggregate substitute impacts concretedensity. Compressive strength tests revealed a reduction of 5.98% in the concrete containing a 25% waste mixture, withaverage compressive strength declining from 307.22 kg/cm² to 288.94 kg/cm². A more pronounced reduction occurred inthe 50% waste mixture, where compressive strength decreased by 15.70% (from 307.22 kg/cm² to 259.06 kg/cm²). Thistrend aligns with the understanding that higher waste content correlates with greater mechanical strength reduction, likelydue to the differing physical properties of waste materials, such as lower density, which impact overall concreteperformance, particularly in compressive strength.